Islam dan Humanism (When Muslim Learns From The West: A Cross Curtural Project) - Anzalman, Anzalman; Kamal, Tamrin; Hakim, Rosniati; Julhadi, Julhadi; Thaheransyah, Thaheransyah; Hanafi, Halim (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2024)
The cross-cultural project of combining Islam and Western humanism is an attempt to explore and integrate humanistic values in an Islamic context. Historically, Muslim intellectual traditions have long interacted with Western thought, from the era of translation of Greek philosophical works to the era of modernization and globalization. This project aims to bridge the gap between the two traditions by identifying universal principles that can be applied in contemporary Muslim societies. Western humanism, which emphasizes individual freedom, human rights and rationality, is often seen as at odds with some traditional interpretations of Islam. However, many Islamic teachings also underscore the importance of human dignity, social justice and moral responsibility. Through dialog and cross-cultural learning, it is hoped that a deeper understanding and harmonious solutions to contemporary challenges faced by Muslim societies can be achieved. This study reviews the history of the relationship between Islam and Western humanism, analyzes the challenges that arise in this integration process, and explores successful examples from Muslim countries such as Turkey and Indonesia. By integrating perspectives from both traditions, this project seeks to create a solid foundation for greater collaboration and understanding, which can ultimately contribute to the creation of a more just, peaceful and humane world.